The Role of the Transorbital Superior Eyelid Approach in the Management of Selected Spheno-orbital Meningiomas: In-Depth Analysis of Indications, Technique, and Outcomes from the Study of a Cohort of 35 Patients - Locatelli, Davide; Restelli, Francesco; Alfiero, Tommaso; Campione, Alberto; Pozzi, Fabio; Balbi, Sergio; Arosio, Alberto; Castelnuovo, Paolo (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective Primary goal in spheno-orbital meningioma (SOM) surgery still remains complete resection. Nevertheless, given their highly infiltrative nature, a growing body of literature suggests to shift toward function-sparing surgeries. We here present our experience in the management of SOMs through the endoscopic superior eyelid approach (SEA).Methods Surgical database from our multidisciplinary work group was retrospectively reviewed to identify patients treated for SOMs in the last 10 years by our senior authors, analyzing and correlating clinical, radiological, and outcome variables among the different approaches used.Results There were 35 patients (mean age of 57.3 ± 12.86 years), with a mean follow-up of 31.5 months (range: 6–84 months). The most common preoperative complaint was proptosis (62.9%) followed by diplopia and visual deficit. Greater and lesser sphenoid wings were the areas mainly involved by the pathology (91.4% and 88.6%, respectively), whereas orbital invasion was evidenced in one-third of cases. Patients were operated on through craniotomic (48.6%), endoscopic superior eyelid (37.1%), and combined cranioendoscopic (14.3%) approaches. Simpson grades 0 to II were accomplished in 46.2% of SEA and 76.5% of craniotomies. All patients with a preoperative visual deficit improved in the postoperative period, independently from the approach used. On patients who underwent endoscopic SEA, there was improved their short-/long-term postoperative Karnofsky Performance Status.Conclusions Endoscopic SEA is a safe and effective alternative to transcranial approaches in very selected cases of SOMs, where the planned primary objective was to obtain a maximally safe resection, aimed at symptom relief, rather than a gross total resection at any cost.
Keywords: meningiomas; transorbital approach; superior eyelid; spheno-orbital meningioma